Typical Hesitant Fuzzy Negations. Issue 6 (June 2014) - Bedregal, Benjamin; Santiago, Regivan H.N.; Bustince, Humberto; Paternain, Daniel; Reiser, Renata; Herrera, F.; Martínez, L.; Torra, V.; Xu, Z.
<x xml:space="preserve">Abstract</x> Since the seminal paper of fuzzy set theory by Zadeh in 1965, many extensions have been proposed to overcome the difficulty for assigning the membership degrees. In recent years, a new extension, the hesitant fuzzy sets, has attracted a lot of interest due to its usefulness to handle those problems in which it is difficult to provide accurately a single membership value; since for hesitant sets, membership values are given by a whole set of values. On the other hand, since fuzzy negations have an important role in applications as well as in the theoretical approach to of fuzzy logics, it is important to study an extension of the concept of fuzzy negation for hesitant fuzzy degrees (elements). In this paper, we propose such a definition and we study some of the main properties of this new concept.